Hubungan Pengetahuan dan Sikap Tentang Gambar Peringatan Kesehatan Pada Kemasan Rokok Dengan Perilaku Merokok Pada Remaja - Merissa Laora Heryanto; Cecep Heriana; Fitri Kurniarahim (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2017)
Introduction : The prevalence of adolescent male smokers aged 15-19 years in Indonesia increased by 13.3% over the period 1995 to 2013. The aim of the study was to determine the relationship of knowledge and attitudes about the picture of health warnings on packs of cigarettes and smoking behavior in adolescents. Methode : The research was conducted in the village Kadugede with cross-sectional study involving 153 male adolescents aged 15-21 years. Result : The results of the bivariate analysis showed a significant relationship knowledge (p = 0.009, CI 95%) and attitude (p = 0.007, 95% CI) of picture health warnings on packs of cigarettes and smoking behavior. Kadugede village is expected to better utilize the results of this study as an information source for directing teens do behavior clean and healthy.